Race, geographical location and other risk factors for hypertension: South African National Health and Nutrition Examination Survey 2011/12 - Sasiragha Priscilla Reddy; Anthony David Mbewu; David R. Williams; Nigel Walsh Harriman; Ronel Sewpaul; Justin Winston Morgan; Sibusiso Sifunda; Thabang Manyaapelo; Musawenkosi Mabaso (Elsevier, 2021)
Background: Hypertension is the leading cardiovascular disease in Africa. It is increasing in prevalence due partly to the epidemiological transition that African countries, including South Africa, are undergoing. This epidemiological transition is characterised by a nutrition transition andurbanisation; resulting in behavioural, environmental and stress changes that are subject to racial and geographic divides. The South African National Health and Nutrition Examination Survey (SANHANES) examined the association of traditional risk factors; and less traditional risk factors such as race, geographical location, social stressors and psychological distress with hypertension in a national population-based sample of South Africans. Methods: Data were analysed on individuals ≥15 years who underwent a physical examination in the SANHANES (n = 7443). Hypertension was defined by blood pressure ≥140/90 mmHg or self-reported hypertension medication usage. Stepwise regression examined the association of demographic, socioeconomic, life stressors, and health risk factors with systolic blood pressure, diastolic blood pressure, and hypertension. Secondly, the risk factor associations and geographical location effects were investigated separately for the African race group. Results: Increasing age (AOR = 1.069, p < 0.001); male gender (AOR = 1.413, p = 0.037); diabetes (AOR = 1.66, p = 0.002); family history of high blood pressure (AOR = 1.721, p < 0.001); and normal weight, overweight and obesity (relative to underweight: AOR = 1.782, p = 0.008; AOR = 2.232, p < 0.001; AOR = 3.874, p < 0.001 respectively) were associated with hypertension. Amongst African participants (n = 5315) age (AOR = 1.068, p < 0.001); male gender (AOR = 1.556, p = 0.001); diabetes (AOR = 1.717, p = 0.002); normal weight, overweight and obesity (relative to underweight: AOR = 1.958, p = 0.006; AOR = 2.118, p = 0.002; AOR = 3.931, p < 0.001); family history of high blood pressure (AOR = 1.485, p = 0.005); and household crowding (AOR = 0.745, p = 0.037) were associated with hypertension. There was a significantly lower prevalence of hypertension in rural informal compared to urban formal settings amongst African participants (AOR = 0.611, p = 0.005). Other social stressors and psychological distress were not significantly associated with hypertension. Conclusion: There was no significant association between social stressors or psychological distress and hypertension. However, the study provides evidence of high-risk groups for whom hypertension screening and management should be prioritised, including older ages, males, people with diabetes or with family history of hypertension, and Africans who live in urban formal localities.